2003
DOI: 10.2105/ajph.93.2.215
|View full text |Cite
|
Sign up to set email alerts
|

Future Directions in Residential Segregation and Health Research: A Multilevel Approach

Abstract: The authors examine the research evidence on the effect of residential segregation on health, identify research gaps, and propose new research directions. Four recommendations are made on the basis of a review of the sociological and social epidemiology literature on residential segregation: (1) develop multilevel research designs to examine the effects of individual, neighborhood, and metropolitan-area factors on health outcomes; (2) continue examining the health effects of residential segregation among Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
338
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 428 publications
(352 citation statements)
references
References 59 publications
13
338
0
1
Order By: Relevance
“…Dissimilarity (i.e., the unevenness of the minority group distribution over the MSA) was excluded because researchers have argued persuasively that this dimension does not have clear conceptual foundations for associations with health. 27,31 Centralization (i.e., the extent to which minority group members reside in the Central Business District) was excluded because recent work has shown that the central city-suburb distinction has become less relevant to racial/ethnic residential patterns. 46 Finally, concentration (i.e., the amount of physical space occupied by minority group members) was excluded because this segregation measure appears to be more relevant to understanding the spread of infectious disease 47,48 than the diffusion of health behaviors such as smoking.…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissimilarity (i.e., the unevenness of the minority group distribution over the MSA) was excluded because researchers have argued persuasively that this dimension does not have clear conceptual foundations for associations with health. 27,31 Centralization (i.e., the extent to which minority group members reside in the Central Business District) was excluded because recent work has shown that the central city-suburb distinction has become less relevant to racial/ethnic residential patterns. 46 Finally, concentration (i.e., the amount of physical space occupied by minority group members) was excluded because this segregation measure appears to be more relevant to understanding the spread of infectious disease 47,48 than the diffusion of health behaviors such as smoking.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Segregation-defined as the spatial separation of one group from another on the basis of race/ethnicity 26,27 -is considered a fundamental cause of the concentrated poverty and health inequalities experienced by African Americans in the US. [28][29][30] While segregation has declined over the last few decades, African Americans remain the most segregated racial/ ethnic minority in the US, and most live in urban areas with high segregation.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] These dimensions of the social environment have well-established relationships to a range of health outcomes, [17][18][19] including cancer-related outcomes. 20 Recent evidence suggests that segregation and local racial composition may also affect disparities in breast cancer outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have tested these pathways to see whether monitoring the quality of a neighborhood can explain the effects of segregation or not. 8 Further studies on the effect of segregation with controlling the concentration of the addressed contextual factors are recommended to test whether segregation of a contextual factor acts through the concentration of that factor or other contextual factors at a provincial level.…”
Section: Resultsmentioning
confidence: 99%
“…It also affects intergroup connections in society. 4 Many papers have explored the effects of living in more segregated communities on health disparities and the links between residential segregation and health outcomes, including the relation between racial residential segregation and overall death, 5,6 tuberculosis, 7 cardiovascular diseases, 8 high body mass index, 9 pre-term birth in black populations, 10 and also social outcomes such as early adolescent sexual activity, 11,12 black homicide rates, 13,14 poor self-rated health, 9,15 access to employment, educational inequalities, crime, and other aspects of social and economical well-being. 16 So far, our literature review has shown that the relation between segregation and disability has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%